Exploring the role of post‐error processing in social anxiety across age. - Stibolt, Olivia A.; Soto, Fabian A.; Pettit, Jeremy W.; Rey, Yasmin; Buzzell, George A. (Journal of Child Psychology & Psychiatry, 2025)
Background: Error monitoring, a neurocognitive process reflecting self‐detection of errors, has been proposed as a marker of social anxiety. However, the way in which this marker relates to social anxiety is not consistent across age, as older children and adolescents with anxiety exhibit heightened error monitoring and younger children with anxiety exhibit diminished error monitoring. One way to contextualize this inconsistency and provide insight into childhood social anxiety is to examine the less‐studied consequences of error monitoring, termed post‐error processing. Methods: We employed computational modeling to estimate a form of post‐error processing (attentional focusing) during a flanker task, within a cross‐sectional sample of 148 treatment‐seeking youth aged 7–17. Youth reported social anxiety symptoms via the Screen for Child Anxiety Related Disorders (SCARED). Results: Mixed‐effects regression analyses revealed a three‐way interaction (p =.034) between trial type (post‐error/correct), age, and social anxiety symptoms predicting attentional focusing. Higher social anxiety predicted diminished post‐error attentional focusing in children, but this effect changed across age, with higher social anxiety no longer predicting diminished post‐error attentional focusing by adolescence. Conclusions: Studying the functional consequences of committing errors (post‐error processing) provides additional context for understanding the relationship between social anxiety and error monitoring. These data elucidate important changes in the relationship between social anxiety and post‐error processing across age and could therefore inform developmentally sensitive treatments of pediatric social anxiety.